A wizard of Mars / 9 - Duane, Diane (Duane, Diane. Young wizards series., 2010)
Young wizards Kit Rodriguez and Nita Callahan join an elite team sent to investigate an ancient Martian race, but after a series of strange events, Kit disappears, and Nita is left to recover her friend and master a power that will help prevent an interplanetary war that could destroy Earth.